(untitled) (Palíndromo, 2024)
This article addresses ways of reading urban visuality, taking walks around the city and the perceptual and affective relationships as a starting point, which build the imaginary, anchored in the history and memory of places. This theme is an excerpt from the proponent’s doctoral research, and deals with the production of meaning in the urban subject, based on their visual, sensorial and synesthetic interactions with the city. Although the focus is on three points in the city of Curitiba, capital of Paraná, the aim is to provoke in the reader reflections on different ways of reading and interacting with the sensitive potential of any and all cities, in their multiple reading possibilities. In the central region, the visual reading of a place listed as a Historical Heritage site is emphasized, and in the neighborhood region, the focus is on the erasure of memory through the ruin and destruction of heritage sites. Halbwachs, Le Goff and Argan address issues of memory and the history of places, just as Freire, Peixoto and Canton dialogue with relationships of affection and urban imagination. These conceptions are based on the phenomenology of Merleau-Ponty and on some concepts of sociosemiotics, specifically Landowski and Oliveira, which base the interactions and aesthetic relations in the production of meaning in the subject of the city.